Free Convective Heat And Mass Transfer Radiative Flow Past An Impulsively Started Vertical Moving Plate With Uniform Heat And Mass Flux - .kodidala,, Janardhan; Pillai.k, Jagadeeswara; Reddy. G, Viswanatha (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this paper, we studied analytically thethermal radiation effect on free convective flow of aviscous incompressible fluid past an impulsively startedvertical plate with flux. The fluid is assumed to be grayabsorbing-emitting but not a scattering medium andRosseland approximation is used to describe the Radiativeheat flux. The method of Laplace transform is used to solvedimensionless governing partial differential equations. Theresulting velocity, temperature and concentration profilesas well as the skin friction, rate of heat and mass transferhave been obtained. Some important applications ofphysical interest for different type motion of the plate arediscussed numerically through graphs.